Macrozoobenthos Community Structure In The Estuary of Donan River, Cilacap, Central Java Province, Indonesia - Taufik Fakih Hakiki; Isdradjad Setyobudiandi; Sulistiono Sulistiono (Journal Omni-Akuatika, 2017)
Estuary of Donan Riverwhich is adjacent to Segara Anakan Lagoon in Cilacap, Central Java Province (Indonesia) has been used for a number of activities such asfishieries, agriculture, industry, harbor, and tourism activities.  The aim of this study is to analyze the ecosystem condition based on mazcrozoobenthos community structure. This study was conducted from Augustus 2015 to January 2016. Samples were collected monthly at five stations from the river close area to the ocean close area. The study was conducted to identify kinds of generaand densityof themacrozoobenthos, and analyze substrates and water quality.Data analysis was performed onabundance, diversity, evenness and dominance indexes.Based on the study, macrozoobenthos at the estuary of Donan River consists of three classes i.e Gastropod (12 genera), Bivalvia(9 genera), and Polychaeta (6 genera). Based on the sampling location, Gastropod and Bivalvia are the largest composition found at five stations. Based on the sampling location, the macrozoobenthos density, diversity index, evennes index,and dominance index can be inferred that the estuary of Donan River is classified to be moderately ecological polluted.